2013
DOI: 10.4236/oje.2013.36045
|View full text |Cite
|
Sign up to set email alerts
|

Has the Luangwa (Zambia) hippopotamus (<i>Hippopotamus amphibius</i>) population stabilized after reaching its asymptote? What are the management challenges?

Abstract: The population size of hippo (Hippopotamus amphibius Linnaeus 1758) in Luangwa valley, Zambia was earlier assessed for the period 1976-2008 and repeated 2009-2012 and found to have reached and maintained carrying capacity K of 6000 individuals over a 165 km river stretch. This study covered the period 2009-2012 and used river bank count method as in previous studies. The method involved counting individuals and taking GPS locations of hippo schools. During the period 2009-2012 the population had maintained irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…At K recruitment rate declines and the composition of calves and sub adults in the population also declines. Similar results were obtained during the 1970-1972 culling programme where there was an under representation of younger age classes (Marshall and Sayer, 1976) which is a true reflection of the population structure, at K (Sensu Chomba et al 2013).…”
Section: Population Statussupporting
confidence: 71%
See 1 more Smart Citation
“…At K recruitment rate declines and the composition of calves and sub adults in the population also declines. Similar results were obtained during the 1970-1972 culling programme where there was an under representation of younger age classes (Marshall and Sayer, 1976) which is a true reflection of the population structure, at K (Sensu Chomba et al 2013).…”
Section: Population Statussupporting
confidence: 71%
“…The hippopotamus population size in the Luangwa River was at ecological carrying capacity K of 6,000 individuals as recorded by Chomba et al (2013). At K recruitment rate declines and the composition of calves and sub adults in the population also declines.…”
Section: Population Statusmentioning
confidence: 93%
“…Moreover, hippos often congregate in large numbers (Fig. 3A) (Chomba, Simpamba & Nyirenda, 2013;Dutton et al, 2018b;Fritsch, Plebani & Downs, 2022), extenuating and amplifying their individual engineering impacts. Lewison (2007) and Lewison & Pluh aček (2017).…”
Section: The Making Of An Ecosystem Engineer: the Case For Hipposmentioning
confidence: 99%
“…The highest hippo population densities are known from the Luangwa River, Zambia, where up to 42 individuals per km of river have been documented (Tembo, 1987; Chomba et al ., 2013). High to moderate hippo densities have also been observed along the Great Ruaha River (26 animals km −1 ; Stears et al ., 2018), Mara River (27 animals km −1 ; Kanga et al ., 2011), Lake Edward (19 animals km −1 shoreline; Lock, 1972), and in Kruger National Park along the Sabie (18 animals km −1 ), Olifants (14 animals km −1 ), and Letaba rivers (13 animals km −1 ) (Smit et al ., 2020).…”
Section: The Making Of An Ecosystem Engineer: the Case For Hipposmentioning
confidence: 99%
“…The area currently holds the largest global hippopotamus population (Lewison, 2007;Chomba et al 2013) and was found suitable for this study. The study covered incidences of mortality on hippopotamus population along the 165 km stretch of the Luangwa River and the associated riverine habitat from the Chibembe pontoon (12 o 48' S, 32 o 03'E) to the Lusangazi -Luangwa confluence (13 o 24' S, 31 o 33' E).…”
Section: 1study Area Location and Descriptionmentioning
confidence: 99%